New Zealand and the origins of of Universal Declaration - Aikman, Colin (Victoria University of Wellington Law Review, 1999)
Dr Aikman here provides a personal perspective on the New Zealand’s role at the United Nations Conference on International Organisation, held at San Francisco in 1945, and at the time of the adoption of the Universal Declaration of Human Rights at the meeting of the United Nations General Assembly, held in Paris in 1948. Dr Aikman was adviser to the member of the New Zealand delegation who presented the New Zealand case at the Paris meeting of the UN General Assembly in September 1948. The author provides New Zealand’s positions on economic and social rights, trade unions, and the right to petition. The author then discusses the adoption of the Declaration, and core conventions which were later adopted. The author concludes with a discussion on the legal status of the Declaration, as well as its Māori translation.